THE IMPROVEMENT OF MATHEMATICS COMMUNICATION FOR JUNIOR HIGH SCHOOL STUDENTS THROUGH CONTEXTUAL MATHEMATICS LEARNING - Herlina Herlina (USN Kolaka, 2016)
This study aims to (1) obtain a mathematical description of the communication skills of students with mathematics learning contextual learning and student learning by conventional teaching; (2) To determine the improvement of communication skillsstudents learn mathematics with math contextual learning and student learning by conventional teaching; (3) In order to obtain comparative increase in mathematical communication skills students learn mathematics contextual learning and student learning by conventional teaching; (4) In order to obtain a description of the activity of students in mathematics learning contextual; (5) In order to obtain a description of what students about math learning contextual. This research was conducted by using a quasi-experimental design with the model of the Non-equivalent Pretest and PosttestControl Group. The population in this study was all students of class VIII SMP Negeri 1 Kolaka with samples of two classes as experimental class and control class. The instrument used in this study consisted of communication test instruments andmathematical abilities nontes instruments, such as observation sheets, and opened questionnaire sheet. The analysis used is descriptive analysis, significant test one sample, and the average difference in of two. The results showed that in general thecontextual learning mathematics can improve communication skills of mathematics. Learning math can be used as an alternative contextual learning for teachers, especially for math students improve communication skills.